Peluang Dan Tantangan Usaha Mikro Kecil Dan Menengah Pada Era Globalisasi Di Desa Mojowatesrejo - Sarbini Sarbini; Athala Rania Insyra; Alvina Fidriyanti; Ismia Rodlotul Jannah; Davit Mahesa Handika; Muhammad Ekky Alfiansyah; Mia Hartatik; Achmad Heri Nurcahyo; Berlinda Sayidah Imamah; Chresta Awaliyah Suntana; Rico Panigoro; Imam Wahyudi; Tri Prasetyo Wahyu; Chindy Kriswahyuni; Mukhammad Saiful Arifin; Lely Dewi Nur Afidah; Zulfa Zulfa; Bagus Pujo Sasongko; Bima Dwi Atmadja; Falah Alifudin Yusuf; Ella Orsita Adelia; M. Fanani; Sukma Fatmawati; Adi Murdiono (Jurnal Nusantara Berbakti, 2024)
This research aims to discuss the opportunities and challenges of the world of work in the era of globalization in Mojowatesrejo village as a driving force for the development of Micro, Small and Medium Enterprises (MSMEs). The research results show that globalization means the process of bringing information, thoughts, lifestyles and technology into the world scope. In the era of globalization, business people have to compete with competitors all over the world. Globalization has expanded markets and reduced geographic boundaries, but it has also increased intense competition. In facing challenges and taking advantage of opportunities, collaboration, innovation and focus on customer needs will be the keys to success. Article 28D paragraph (1) Every person has the right to recognition, guarantees, protection and fair legal certainty as well as equal treatment before the law.